Development of an enterprise engineering strategy execution framework - Mudavanhu, Thabani B. (University of the Witwatersrand, Johannesburg, 2024)
Even with a myriad of implementation models from consulting firms and academia – the success rate of Strategy Execution (SE) remains low. Extant literature in strategy execution exposes inadequacies of theoretical foundations for the assertions outlined in current SE models. In addition to this, where there is some explanation, the theory is inconsistent, and discipline biased which limits development of general application theory. Further to this ‘enterprises’ as the housing (the system of interest) from which a strategy is launched rarely receive the level of attention and rigor that technical systems do. Against this background, this study sought to understand how the success rate of SE can be improved through the application of Enterprise Engineering (EE) principles and practices. The premise being that the challenges in implementing strategies in any organisation are too an extent related to the design of the enterprise. Consequently, the common challenges attributed to the failure in SE can be linked to the enterprise design and as such organisations can, to an extent be designed to influence SE. Considering the complexity / greyness of the study area and limited literature in the relatively new discipline of EE, specifically enterprise ontology theory (the theoretical lens of this study), a structured literature review was used as the basis for a Delphi study. A two (2) round Delphi study was conducted with experts in the field to determine and validate the critical dimensions in Strategy Execution. Thirty-one (31) and twenty (25) experts participated in Delphi Round 1 and 2 respectively. The experts came from four regions of the world and were largely academics, board members and executive leaders and practitioners many of them tasked with either overseeing or leading strategy execution. The study revealed that there is a significant relationship between the design of an enterprise at the deepest level (the ontological layer) and the seven (7) aggregated themes that were synthesised in this study and are linked to constraining successful SE – (a) the strategy itself, (b) leadership, (c) people (the team); (d) effective communication; (e) organisational capabilities (f) organisational enablers and (g) organisational culture. The study proposed a generic enterprise engineering-based strategy execution (EEbSE) framework anchored in the deepest layer of an organisation, the ontological layer - the level where companies transact (cooperate and enter into agreements). Consequently, the study confirmed the proposition that ‘organisations can, to some degree, be designed or re-engineered for strategy execution’. This study demonstrates how EE can be useful in aiding Successful SE. An example of a key take-away include the need to check for execution readiness at the ontological layer and v eliminating any construction flaws (errors) that will later reflect as ‘common’ challenges. For example, lack of commitment [people issues] and lack of an implementation [culture issues] are flaws associated with SE that can be traced and re-engineered at the ontological level. This study adds to on-going work to confront the SE challenge and demonstrates the relevancy and pervasiveness of the application of EE.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Strategy Execution; Strategy Implementation; Enterprise Engineering; Enterprise Ontology; SDG-8: Decent work and economic growth